Theory, activities, and variable characteristics of nature-based interventions and related research among Korean workers: A scoping review - Jeong-Hee Kim; Young Suk Park; Ji-Boo Park (The Journal of Korean Academic Society of Nursing Education, 2026)
Purpose: Nature-based interventions have increasingly been explored as strategies to promote workers’ health and well-being. However, both the characteristics of such research and its practical application among Korean workers have not been systematically examined. This study aimed to conduct a scoping review of nature-based interventions and related research in this population.Methods: Following the Joanna Briggs Institute guidelines for scoping reviews, studies were searched in three databases: RISS (Research Information Sharing Service), DBpia, and ScienceON. Studies published in KCI (Korea Citation Index)-indexed journals were included. A total of 41 studies were analyzed to identify research trends, theoretical frameworks, types of nature, applied activities, and related variables at the individual, job, and organizational levels.Results: Nature-based interventions and related research among workers have grown steadily since 2011, accompanied by an increasing number of experimental studies evaluating intervention effects. However, despite this progress, the explicit application of theoretical frameworks and the integration of job- and organizational-level contextual factors remain limited. Most studies have focused on green spaces, while research addressing diverse natural environments, including blue spaces, was scarce. Furthermore, the literature has primarily examined individual-level psychosocial and physiological outcomes, with comparatively little attention given to job- and organizational-level variables.Conclusion: Although nature-based interventions and related research among Korean workers are increasing, further studies are warranted to strengthen theoretical frameworks, incorporate job and organizational context variables, and explore diverse types of nature to optimize the development and efficacy of nature-based strategies for workplace health promotion.